PRZEGLĄD PIŚMIENNICTWA - Staniszewska, Danuta (Wydział Prawa i Administracji UAM, 1998)
Transition Banking. Financial Development of Central and Eastern Europe, pod red. Ronalda W. Andersona i Chantal Kegels, Clarendon Press, Oxford 1998, ss. 300.